Digital Media-Assisted Project-Based Assessment for Enhancing Responsibility and Collaboration in Elementary Social Studies Learning - Ni Komang Widiani; Ni Nyoman Rediani (Journal of Education Technology, 2026)
Elementary Social Studies learning still faces challenges in developing students’ responsibility and collaboration because assessment practices tend to emphasize cognitive outcomes rather than affective and social competencies. This study aims to analyze the effectiveness of digital media-assisted Project-Based Assessment in improving students’ responsibility and collaboration in elementary Social Studies learning. This study employed a quasi-experimental design using a non-equivalent post-test only control group design. The sample consisted of fourth-grade students from two elementary schools in Kubutambahan District, namely 20 students in the experimental group and 18 students in the control group. Data were collected using questionnaires and observation sheets that had been tested for validity and reliability. Data were analyzed using descriptive statistics and MANOVA after meeting the assumptions of normality, homogeneity, covariance matrix homogeneity, and multicollinearity. The results showed that students in the experimental group obtained higher mean scores than those in the control group for responsibility and collaboration. The MANOVA results indicated a significant simultaneous effect of digital media-assisted Project-Based Assessment on both variables. The Tests of Between-Subjects Effects also showed significant partial effects on responsibility and collaboration, with responsibility showing a stronger improvement. These findings indicate that digital media-assisted Project-Based Assessment is effective in developing students’ affective and social competencies.